Implementasi Manajemen Tatalaksana Pendidikan dalam Meningkatkan Layanan Pembelajaran di Sekolah / Madrasah - Adib Habibi (STAI Terpadu Yogyakarta, 2019)
Education Management or commonly called Administration is one of the supporting work units in the organization and has a strategic position in achieving organizational goals. With the duties and functions of the Education Management System as a supporting unit that makes this unit as important as other units within the organization. Because of that, the logical consequence of the importance of administrative services from governance is as the main management wheel of the institution's important internal files. If there is a small amount of distribution and management, it will be fatal in the next process, namely the implementation of overall organizational activities. Even in the ongoing education process. The reality in the field that we often encounter, especially in private education institutions is that there are many administrative staff who are also teaching assignments or vice versa. With the pretext of funding efficiency and optimizing the potential of HR. This is what makes Trueble Maker, the dualism of different work practices carried out simultaneously in the same institution.The practice of HR management that is chaotic above is fatal to the management of the internal files of the institution. So that the management (management) of HR in the field of management is guaranteed to be a safe and neat file validity in order to continue the process of better organizational wheel organization.